Evaluating a benchtop fermentation method for estimating dextrin degradation by hop diastatic enzymes during dry-hopping - Stokholm, Arnbjørn; Rubottom, Lindsey N.; Shellhammer, Thomas H. (BrewingScience, 2020)
HOP SPECALDry-hop creep is a gradual reduction in beer gravity after dry-hopping in the presence of yeast due to generation of fermentable sugars from nonfermentable dextrins by hop-associated enzymes. A benchtop forced fermentation-based method for estimating the dextrin reducing potential of hops during dry-hopping is proposed and evaluated for feasibility. In this paper, forced fermentations are compared to paired 2 hL pilot full-scale fermentations in order to evaluate how well a benchtop method will reflect the changes observed due to hop creep in a full-scale fermentation. The forced fermentations proceeded much more rapidly than the full-scale pilot fermentations, and apparent extract and apparent degree of fermentation correlated well between the dry hopped forced fermentations as measured at 72 hours and the terminal values of the full-scale fermentations. Results indicate that a small-scale dry-hopped forced fermentation is a promising tool for assessing the potential magnitude of hop creep in a given lot of hops, and that differences in apparent extract and/or apparent degree of fermentation of forced fermentations can be used to estimate the terminal gravity post-hop creep of full-scale fermentations.